Trafficking to uncharted territory of the nuclear envelope - Burns, Laura T (2012)
The nuclear envelope (NE) in eukaryotic cells serves as the physical barrier between the nucleus and cytoplasm. Until recently, mechanisms for establishing the composition of the inner nuclear membrane (INM) remained uncharted. Current findings uncover multiple pathways for trafficking of integral and peripheral INM proteins. A major route for INM protein transport occurs through the nuclear pore complexes (NPCs) with additional requirements for nuclear localization sequences, transport receptors, and Ran-GTP. Studies also reveal a putative NPC-independent vesicular pathway for NE trafficking. INM perturbations lead to changes in nuclear physiology highlighting the potential human disease impacts of continued NE discoveries.